Using Sem To Interpret The Relation Sheep Between Organization Learning - Medini ,Atmane; Chekka ,Abdallah (جامعة الوادي University of Eloued, 2024)
The study aims to reveal the interactive relationship between the levels of individual learning, group learning, and organizational learning and their impact on performance by including non-traditional dimensions in the research instrument. The instrument, in the form of a questionnaire, explored the latent dimensions of a sample of employees and workers in a banking unit of Al Baraka Bank in Algeria. Structural equation modelling (SEM) was employed to analyze the data, and the results revealed an absolute absence of the impact of individual efficiency in creating collective value, which negatively affects the performance levels of the bank, explaining the decline in the performance of the Algerian banking sector as a whole.
Using SEM to interpret the relation sheep between organization learning and performance – Albaraka bank case
Keywords: individual learning; Collective learning; organizational learning; SEM; economic value